Acciones para reivindicar el futuro de la educación artística en secundaria : el proyecto second round - Huerta, Ricard (2018)
The situation of Art Education in the Spanish panorama, especially in Secondary School (the only non-university studies with specialist) through a delicate and complex moment. In front to the possibility that this discipline curriculum removed, from the university we encourage the creation of associations from teaching staff. Among the protest actions highlights the Second Round Project